Theoretical investigation of an atomic Fabry Perot interferometer based acceleration sensor for microgravity environments - Manju Perumbil; Matthew J. Blacker; Stuart S. Szigeti; Simon A. Haine (npj Microgravity)
Abstract We investigate the use of an atomic Fabry-Perot interferometer (FPI) with a pulsed non-interacting Bose-Einstein condensate (BEC) source as a space-based acceleration sensor. We derive an analytic approximation for the device’s transmission under a uniform acceleration, which we use to compute the device’s attainable acceleration sensitivity using the classical Fisher information. In the ideal case of a high-finesse FPI and an infinitely narrow momentum width atomic source, we find that when the device length is limited, the atomic FPI can achieve greater acceleration sensitivity than a Mach-Zender (MZ) interferometer of equivalent device length. Under the more realistic case of a finite momentum width source, we identify the ideal cavity length for the best sensitivity. Although the MZ interferometer now offers enhanced sensitivity within currently achievable parameter regimes, our analysis demonstrates that the atomic FPI holds potential as a promising future alternative if narrow momentum width atomic sources can be engineered.